CYP2A6 Gene Polymorphism Allele *4 Study in Hypertensive Patients with a History of Smoking - Rahayu Sudarsono, Erica Kusuma; Christine Patramurti (Eureka Herba Indonesia, 2023)
Nicotine is a specific CYP2A6 substrate found in cigarettes. Nicotine levels in the blood are affected by the metabolic rate of the CYP2A6 enzyme, which is known to have a high level of polymorphism. High levels of nicotine in the blood can result in an increased risk of cardiovascular disease through the mechanism of increasing lipolysis and causing an increase in triglyceride levels in the blood. This study is an observational study conducted on 31 hypertensive men with a history of smoking. The purpose of this study was to determine the frequency of the CYP2A6 allele *4 genes in hypertensive patients with a history of smoking. Result analysis was performed on PCR products using electrophoresis, then the frequency of each allele was determined. The results showed that there was a CYP2A6 allele *4 gene in hypertensive patients with a history of smoking in Yogyakarta with an allele frequency of 62.90%, and only 2 respondents (6.45%) had the CYP2A6*1/*1 genotype or wildtype.